2008
DOI: 10.1007/s10404-008-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a continuous microfluidic rheometer

Abstract: In a previous paper we presented a way to measure the rheological properties of complex fluids on a microfluidic chip (Guillot et al., Langmuir 22:6438, 2006). The principle of our method is to use parallel flows between two immiscible fluids as a pressure sensor. In fact, in a such flow, both fluids flow side by side and the size occupied by each fluid stream depends only on both flow rates and on both viscosities. We use this property to measure the viscosity of one fluid knowing the viscosity of the other o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
(33 reference statements)
1
18
0
2
Order By: Relevance
“…It was not absolute flow rates but the phase ratio determining the interface location in a certain microchannel, as shown in Fig. 3, which is accordant with the conclusion drawn by Guillot et al (2008). In Fig.…”
Section: Conditions For Plf Formingsupporting
confidence: 92%
“…It was not absolute flow rates but the phase ratio determining the interface location in a certain microchannel, as shown in Fig. 3, which is accordant with the conclusion drawn by Guillot et al (2008). In Fig.…”
Section: Conditions For Plf Formingsupporting
confidence: 92%
“…The significantly reduced quantity of sample consumption and increased rate of heat/mass transfer and chemical reactions are the key advantages of microfluidic devices. Applications range from pH and temperature sensors to fluid actuators, such as micronozzels, micropumps (Laser and Santiago, 2004;Woias, 2005), micromixers (Hessel et al, 2005;Nguyen and Wu, 2005), microvalves (Kwong and Chong, 2006), micro-rheometers (Guillot et al, 2008), biotechnology areas such as the analysis of DNA and proteins, and biodefence (Whitsides and Stroock, 2001), as well as LOC systems for drug delivery, chemical analysis, and biomedical diagnosis (Bousse et al, 2000). A blood analyzer MEMS requires taking a sample by means of generating blood flow through a microneedle of the microfluidic system.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations at higher length scales clearly showed that particular movement. The position of the interface between two Newtonian fluids was the same with various flow rates, as long as the ratio between then remained constant, which was also noted by Guillot et al (2008).…”
Section: Discussionmentioning
confidence: 82%
“…Lu et al (2011) acknowledged parallel laminar flow for being an effective platform for enhanced mass transfer, for simultaneous preservation of separate phases, for fast phase equilibrium or diffusivity determination with trace chemical consumption, and for continuous, efficient and even multi-stage industrial extraction techniques. Münchow et al (2007) utilized parallel flow for electrophoretic partitioning of proteins and Guillot et al (2008) developed a method to perform automated rheological measurements on a microfluidic chip. They also numerically calculated the steady-state developed velocity profiles for two-phase parallel flow and Galambos and Forster (1998) used an analytical solution of simplified Navier-Stokes equations to obtain the velocity profile at steady-state and to predict the position of the interface of developed flow.…”
Section: Introductionmentioning
confidence: 99%